Failure Modelling of Woven GFRP Bolted Joints under Quasi-Static Loading - Ahmad, Mohd Hilton; D. Crocombe, Andrew; A. Smith, Paul (International Journal of Integrated Engineering, 2013)
Current work concentrates in modelling failure and damage of various woven fabric reinforcement system taken from selected literatures. Experimental observations under quasi-static loading revealed that initial failure occurs at notch vicinity consist of one or combinations of matrix cracking, splitting and laminate de-lamination. The crack then propagated along net-section of distance of about one notch radius size, which thereafter occurrence usually corresponds to catastrophic failures that seen significant tow fractures. The distance of cracked zone signifies ultimate material failure usually referred as “effective damage zone” that useful to be implemented within fracture mechanics concept. These complex morphologies mechanisms can be represented by implementing physically-based constitutive model. Series works of notched woven fabric composite systems plate were implemented within two-dimensional extended finite element method (XFEM) framework were carried out by implementing constitutive models based on basic material properties data of respective system. Good agreement is shown in comparison with experimental data in various and other closed-form approaches composite fabric systems.